arata ca:
a) (3x+4y)^2+(3y-4x)^2=(3^2+4^2)(x^2+y^2)
Răspunsuri la întrebare
Răspuns de
2
Poftim
Sper sa intelegi
Sper sa intelegi
Anexe:
Răspuns de
1
= (9x^2+ 24xy +16t^2 )+ (9y^2-24xy+16x^2)= (9+16)(x^2+y^2)
= 25x^2 + 25y^25= 25(x^2+ y^2)
= 25^2+25y^2= 25x^2+25y^2. ###
= 25x^2 + 25y^25= 25(x^2+ y^2)
= 25^2+25y^2= 25x^2+25y^2. ###
Alte întrebări interesante
Biologie,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă